Pengaruh Likuiditas dan Profitabilitas Terhadap Nilai Perusahaan - Mia Novianti; Dirvi Surya Abbas; Triana Zuhrotun Aulia (Jurnal Mutiara Ilmu Akuntansi, 2024)
This study aims to examine the effect of liquidity and profitability on firm value in companies listed on the Indonesia Stock Exchange (IDX). This research was conducted using secondary data obtained from the official website of the Indonesia Stock Exchange, namely www.id.co.id. The sample in this study amounted to 10 manufacturing companies in the industrial and chemical sectors in the 2018-2021 period. The method used in this research is purposive sampling method. The independent variables used in this study are Liquidity and Profitability, while the dependent variable used in this study is Firm Value. Data were analyzed using multiple linear regression test and firm value was measured using PBV, hypothesis testing was carried out by partial test (t test). The results of this study indicate that liquidity and profitability have an effect on firm value.